Identification of the apparent carrier in mycolic acid synthesis. - Besra, G S (1994)
The mycolic acids are large (C70-90) alpha-alkyl, beta-hydroxy fatty acids and are the major determinants of the mycobacterial cell wall's impermeable barrier. The biosynthesis of mycolic acids is barely understood (they are probably the products of specialized elongation and Claisen-type condensation), and yet their synthesis is the site of action of several mainline antituberculosis drugs. We describe the isolation from Mycobacterium smegmatis and the full characterization of a 6-O-mycolyl-beta-D-mannopyranosyl-1-monophosphoryl-3,7,11,15,19,23 ,27- heptamethyl-(2Z,6E,10E)-octacosatrien-1-ol . The identification of a mycolyl-mannosylphosphopolyprenol supported by cell-free labeling experiments and earlier literature suggests unusual biochemical pathways in which mature mycolic acids are formed from beta-oxo precursors while attached to a mannosyl-P-polyprenol, in which form they are transported through the membrane prior to final deposition as arabinan-bound mycolates.